Enhanced Enzymatic Activity of Laccase (from Pycnoporus sanguineus CS43) Immobilized on Sputtered Nanostructured Gold Thin Films - Rodríguez-Delgado, Melissa; Ornelas-Soto, Nancy; Martínez-Lorán, Erick; Hernandez-Luna, Carlos; García-García, Alejandra; Contreras-Torres, Flavio F (Journal of nanoscience and nanotechnology, 2017)
Functionalization of thin films with organic ligands has been the subject of intense research due to their potential application as heterogeneous molecular nanosystems. In this work, self-assembled monolayers of thiols (16-mercaptohexadecanoic acid and 11-mercaptoundecanol) were used to bind laccase (from Pycnoporus sanguineus CS43) to nanostructured gold thin films obtained by DC sputtering. Sputtering power, sputtering pressure and substrate temperature were optimized to enhance the activity of the immobilized biomolecules. Scanning electron microscopy, confocal microscopy, X-ray diffraction and UV-vis spectroscopy were used to characterize the SAM-functionalized gold substrates. Our results demonstrate that the highest immobilized enzyme activity values can be achieved on substrates of surface roughness ˜200 nm and Au particle size of about 14 nm. The outstanding quality of the as-prepared substrates makes them particularly attractive as bionanosensors.